Exposure of the Gestating Mother to Sympathetic Stress Modifies the Cardiovascular Function of the Progeny in Male Rats - Barra-Pezo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Background: Sympathetic stress stimulates norepinephrine (NE) release from sympathetic nerves. During pregnancy, it modifies the fetal environment, increases NE to the fetus through the placental NE transporter, and affects adult physiological functions. Gestating rats were exposed to stress, and then the heart function and sensitivity to in vivo adrenergic stimulation were studied in male progeny. Methods: Pregnant Sprague–Dawley rats were exposed to cold stress (4 °C/3 h/day); rats’ male progeny were euthanized at 20 and 60 days old, and their hearts were used to determine the β-adrenergic receptor (βAR) (radioligand binding) and NE concentration. The in vivo arterial pressure response to isoproterenol (ISO, 1 mg/kg weight/day/10 days) was monitored in real time (microchip in the descending aorta). Results: Stressed male progeny presented no differences in ventricular weight, the cardiac NE was lower, and high corticosterone plasma levels were recorded at 20 and 60 days old. The relative abundance of β1 adrenergic receptors decreased by 36% and 45%, respectively (p < 0.01), determined by Western blot analysis without changes in β2 adrenergic receptors. A decrease in the ratio between β1/β2 receptors was found. Displacement of 3H-dihydroalprenolol (DHA) from a membrane fraction with propranolol (β antagonist), atenolol (β1 antagonist), or zinterol (β2 agonist) shows decreased affinity but no changes in the β-adrenergic receptor number. In vivo exposure to ISO to induce a β-adrenergic overload provoked death in 50% of stressed males by day 3 of ISO treatment. Conclusion: These data suggest permanent changes to the heart’s adrenergic response after rat progeny were stressed in the uterus. © 2023 by the authors.